1996
DOI: 10.1021/ie9506779
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Propane over Molybdenum Supported on MgO−γ-Al2O3

Abstract: Catalysts of Mo supported on MgO−γ Al2O3 were studied in the oxidative dehydrogenation of propane to propene. The catalysts were active and very stable, but the dehydrogenation selectivity was reduced by the formation of carbon oxides. Characterizations by XRD, XPS, Raman spectroscopy, electron paramagnetic resonance, and BET surface measurements were performed. The catalyst preparation method led to large and stable magnesium molybdate particles on the surface. EPR and XPS measurements gave clues about the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
2
12
0
4
Order By: Relevance
“…As such, the coke generated during the reaction must also be catalytically active. This finding is consistent with past studies that have shown that so-called "active coke" may play a primary role in the dehydrogenation reaction [29][30][31]. The specific surface area is therefore the main factor affecting the catalytic activity.…”
Section: Factors Affecting the Catalytic Activity Of Carbon Catalystssupporting
confidence: 92%
See 1 more Smart Citation
“…As such, the coke generated during the reaction must also be catalytically active. This finding is consistent with past studies that have shown that so-called "active coke" may play a primary role in the dehydrogenation reaction [29][30][31]. The specific surface area is therefore the main factor affecting the catalytic activity.…”
Section: Factors Affecting the Catalytic Activity Of Carbon Catalystssupporting
confidence: 92%
“…Recent advances, however, suggest that various forms of carbon, such as activated carbon [20,21], carbon nanotubes [22][23][24], graphitic carbon [17,25], graphene [22,26], and nanodiamonds [23,27,28], can themselves act as catalysts generating high selectivity and stability during the oxidative dehydrogenation (ODH) reactions of alkanes. Some researchers have even suggested that, in the case of metal-based catalytic systems, the "active coke" formed during the initial stage of the reaction plays a primary role in the ODH process [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…29 Neste sistema, a natureza do suporte controla as espécies VMgO formadas sobre a superfície, enquanto que o desempenho catalítico é determinado principalmente pela composição química através da relação entre Mg/V. 30 Estudos sobre sistemas catalíticos VO x /suporte na reação de desidrogenação oxidativa de alcanos leves, segue um mecanismo redox proposto por Mars e Van Krevelen, 31 no qual a ativação da ligação C-H do alcano pelos centros ativos do óxido metálico, requer a existência de uma afinidade do tipo ácido-base que promova uma aproximação entre o alcano e a superfície do catalisador. 32 Nesse mecanismo, a ativação da ligação C-H ocorre de forma irreversível através das espécies VO x superficiais, mediante oxigênios da rede e grupos hidróxidos superficiais terminais.…”
Section: Introductionunclassified
“…The oxidative dehydrogenation of propane to propylene has been studied using vanadium-and molybdenum-oxidebased catalysts [7][8][9][10][11][12][13][14][15][16][17]. The reaction is believed to proceed by a Mars-van Krevelen reaction mechanism [18][19][20][21][22][23][24], in which adsorbed propane reacts with lattice oxygen and the reduced metal oxide reacts with adsorbed, dissociated O 2 [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated that magnesium molybdates exhibit higher selectivities but lower activities compared to those of the magnesium vanadates [14,15,[33][34][35][36]. Interestingly, each of these reports describes an improvement in the catalytic activity of MgMoO 4 with a slight excess of molybdenum oxide.…”
Section: Introductionmentioning
confidence: 99%